The Semantic Behaviour of Verbs of Emotion in Arabic - Alshdaifat, Abdallah (Dirasat: Human and Social Sciences, 2021)
This study aims to explore the semantic characteristics of verbs of emotion in Arabic by providing a multi-level analysis that involves three levels: examining the compatibility between the default meaning of morphological verbal forms and the derived emotional verbs; investigating thematic roles’ representation of the derived verbal forms; and determining the existence of semantic change in the derived verbal forms. The study found that the derived verbs of emotions are compatible with certain default meanings of the morphological forms among other meanings. For instance, Form II is mainly compatible with the causative meaning, while Form X verbs of emotion tend to express the basic meaning of emotions that can be found in Form I verbs. The thematic roles that are assigned to the syntactic arguments of verbs of emotions are experiencer and stimulus. There are many cases of semantic change, in which derived verbal forms, that belong to emotional roots, leave the semantic field of emotions to other semantic fields. The implications of this study will be useful to research on verbs belonging to other semantic fields. It is also important to develop a WordNet application of emotions.